2020
DOI: 10.1097/md.0000000000019270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and validation of the prognostic value of nutrition and immunity parameters in gastric cancer after R0 resection

Abstract: Precise predictive tools are critical for choosing the individualized treatment protocols and follow-up procedures for patients with gastric cancer (GC). In this study, we aimed to evaluate and validate the prognostic abilities of preoperative nutrition and immunity parameters in GC after curative R0 resection. We established two nomograms based on 437 patients who underwent curative radical gastrectomy for gastric cancer to predict the postoperative overall survival (OS) and recurrence-free surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The cut-off value for AGR ranged from 1.14 to 1.93. All studies reported the association between AGR and OS, and four ( 11 , 13 , 14 , 19 ) reported the association between AGR and DFS or AGR and PFS. Ten of studies were published in English, two ( 12 , 16 ) in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…The cut-off value for AGR ranged from 1.14 to 1.93. All studies reported the association between AGR and OS, and four ( 11 , 13 , 14 , 19 ) reported the association between AGR and DFS or AGR and PFS. Ten of studies were published in English, two ( 12 , 16 ) in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have identified that the tumor-or nutrition-associated factors and host immunity strongly affect the prognoses in patients with cancer [13][14][15]. Thus, Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The DCA results show that the nomogram we developed has good clinical practical value. Recently, some nomograms containing various input variables have been developed to predict the prognosis of different digestive tract tumors [19][20][21][22] . Kim et al 19 developed and validated a nomogram that predicted the risk of lymph node metastasis in patients with early gastric cancer and could be used to avoid unnecessary gastrectomy after endoscopic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing 9,026 patients with metastatic esophageal cancer between 2010 and 2015, Zhu et al 20 found that the nomogram was better at predicting distant metastasis of esophageal cancer than traditional TNM staging. Similarly, the nomogram developed by Xue et al 21 that includes nutritional and immune parameters can effectively predict the overall and postoperative survival rate and relapse-free survival of gastric cancer patients after radical gastrectomy, and its prediction accuracy and discrimination ability are better than those of TNM staging.…”
Section: Discussionmentioning
confidence: 99%